2021
DOI: 10.1136/bmj.n379
|View full text |Cite
|
Sign up to set email alerts
|

Screening and management of atrial fibrillation in primary care

Abstract: Atrial fibrillation is a common chronic disease seen in primary care offices, emergency departments, inpatient hospital services, and many subspecialty practices. Atrial fibrillation care is complicated and multifaceted, and, at various points, clinicians may see it as a consequence and cause of multi-morbidity, as a silent driver of stroke risk, as a bellwether of an acute medical illness, or as a primary rhythm disturbance that requires targeted treatment. Primary care physicians in particular must navigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 176 publications
(206 reference statements)
0
5
0
Order By: Relevance
“… 21 , 22 However, the public health relevance of targeted screening to detect AF in low-resource settings such as China is uncertain. 23 …”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 However, the public health relevance of targeted screening to detect AF in low-resource settings such as China is uncertain. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Pharmacist-led atrial fibrillation screening programmes appear to have demonstrated feasibility across a variety of clinical and non-clinical settings, [4][5][6][7][8][9][10][11][12][14][15][16] To be valuable, any screening programme must be precise, and there must be a robust infrastructure to support effective and safe referral and follow-up in the event of positive screening. 56 There is a paucity of cost-effectiveness data to accompany the studies, and use of a cross-sectional design limited study follow-up, for example, not all studies quantified the number of new atrial fibrillation cases. To support implementation of atrial fibrillation screening programmes, studies need to demonstrate that the associated expenditure translates into a reduced burden on health and social care services.…”
Section: Discussionmentioning
confidence: 99%
“…With a low threshold for patient encounters, and with medical specialists reporting their findings back to primary care, general practitioners (GPs) are well situated for early signalling of symptoms of progressing cardiovascular disease, as well as for having an adequate overview of patients’ risk factors. 5 Furthermore, primary care is important for the follow-up of chronic diseases and for supporting treatment adherence, including in AF. This makes primary care one of the settings with high opportunities to perform screening interventions for AF.…”
Section: Introductionmentioning
confidence: 99%